Detection and molecular characterization of a new genotype of infectious bursal disease virus in Portugal. Issue 1 (2nd January 2022) - Legnardi, Matteo; Franzo, Giovanni; Tucciarone, Claudia Maria; Koutoulis, Konstantinos; Duarte, Isabel; Silva, Marco; Le Tallec, Bertrand; Cecchinato, Mattia
ABSTRACT: Infectious bursal disease virus (IBDV) is an immunosuppressive pathogen with a bi-segmented, double-stranded RNA genome. Two serotypes, named 1 and 2, are recognized, and serotype 1 is traditionally divided into classical, variant and very virulent strains. Despite having great practical relevance, this classification lacks standardization and may therefore generate confusion. The widespread adoption of molecular techniques, which allow direct assessment of either pathogenicity or antigenicity, further complicates this scenario. Recently, two phylogeny-based classification methods have been proposed to obtain informative and standardized results. The first is based on the analysis of the capsid protein VP2 gene, considered as the main determinant of virulence, while the other one considers both VP2 and RNA polymerase VP1, located in different genome segments. The latter approach is therefore better suited to detect reassortment events, which play a significant role in IBDV evolution. This work reports the detection of eight strains in Portuguese broiler farms that diverged from all available IBDV sequences. Subsequent analyses of VP1 and VP2 sequences confirmed that these strains form a new genotype having segment A of a new genogroup and segment B of classical-like genogroup. No recombination events were identified, while several unique amino acid changes were found in key positions within the VP2. This discovery emphasizes the importance of steady and attentive monitoring of IBDV epidemiology. Further research efforts will be devoted to characterizing the novel genotype, by isolating new strains, assessing their pathogenicity and determining the level of protection ensured by commonly administered IBDV vaccines. RESEARCH HIGHLIGHTS: Eight IBDV strains with unique VP2 features were detected in Portugal. Based on two distinct classification methods, the strains belong to a new genotype.